Saccharomyces Boulardii Vs. Yogurt Fluid for Acute Diarrhoea: A Clinical Efficacy Comparison - Saima Tabassum, Hafiz Haseeb Hanif, Sohaib Riaz, Nabeel Ahmed, Muhammad Ahsan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare clinical efficacy of Saccharomyces Boulardii vs. Yogurt Fluid for acute diarrhoea. Methodology: We enrolled 100 cases of acute non-bloody diarrhoea (regardless of gender) between 6 months and 2 years of age in which the duration of diarrhoea was less than 14 days from Madinah teaching hospital, Faisalabad during March till September, 2022. Cases were randomly classified into (A) and (B). Group A received Saccharomyces boulardii (250mg BD for five days) whereas Group B received yoghurt fluid (15 mL twice a day for toddlers 2 years and 30 mL twice a day for children 2 years). Both groups were rehydrated and fed. Clinical effectiveness was 3 stools or fewer each day till day 5. Results: In our study, mean age in Group A was 12.36+4.35 months and in Group B 12.96+5.12 months, p-value=0.529, mean No. of stools before treatment was 7.36+1.21 in Group A and 7.50+1.22 in Group B, p-value=0.565, which reduced to 4.38+1.37 in Group A and 5.24+1.00 in Group B, p-value=0.001. Gender distribution shows that male were 57(57%) and 43(43%) were females. Comparison of clinical efficacy shows that 32(64%) in Group A and 21(42%) in Group-B, p-value=0.022 showing a significant difference. Conclusion: We found that Saccharomyces Boulardi had a much better clinical effectiveness than yoghurt fluid in treating acute diarrhoea in children without blood. Keywords: Children, acute diarrhoea, Saccharomyces Boulardii, Yogurt Fluid, clinical efficacy